Progesterone receptors: Their localization, binding activity and expression in the pig oviduct during follicular and luteal phases - Peralta, Luisa E. (2005)
Estrogens (E) and progesterone (P) are known to require their respective steroid receptors in order to exert structural and functional effects on the oviduct. Cyclic changes in progesterone receptor (PR) localization in the oviductal tissue of female pigs were determined using an immunohistochemical technique with mouse monoclonal antibody mPRI against PR. The variations observed during the estrous cycle in the progesterone receptor (PR) intensity and proportion between ampulla and isthmus probably reflect different response of these regions to progesterone. Immediately before ovulation, during follicular phase, no staining was observed in either the ampulla or the isthmus stroma. However, a low expression of PR in the epithelium of the ampulla was observed. After ovulation, during luteal phase, PR immunostaining was more intense in the whole oviduct. According to immunohistochemical assays, the binding assays for nuclear and cytosolic PR (PRn and PRc, respectively), by using [3H] R5020 at 4°C for 15 h, also showed a higher specific binding during luteal phase. However, the PR mRNA in the oviduct, analyzed by RT-PCR, showed similar levels at both stages of the estrous cycle. Although this methods could not be quantitative, indicate the possibility that a post-transcriptional control could differentially regulate the PR in the pig oviduct.